Improving image quality of mid‐trimester fetal sonography in obese women: role of ultrasound propagation velocity. (5th December 2018) - Chauveau, B.; Auclair, C.; Legrand, A.; Mangione, R.; Gerbaud, L.; Vendittelli, F.; Boyer, L.; Lémery, D.
ABSTRACT: Objective: The quality of ultrasound images is impaired in obese patients. All ultrasound scanners are calibrated for an ultrasound propagation velocity of 1540 m/s, but the propagation in fatty tissue is slower (in the order of 1450 m/s). The main objective of this study was to evaluate the quality of images obtained with different ultrasound propagation velocity settings during the mid‐trimester fetal ultrasound examination in obese patients. Methods: This was a cross‐sectional study using image sets of four recommended scanning planes collected from 32 obese pregnant women during their mid‐trimester fetal scan. Each image set comprised three images obtained successively at three different propagation velocity settings (1540 m/s, 1480 m/s and 1420 m/s). A panel of 114 experts assessed the quality of 100 image sets, grading them from A (most acceptable) to C (least acceptable). Scanning‐plane‐specific indicators of adiposity (fatty layer thickness, probe‐to‐organ distance) were analyzed for each scanning plane. Results: The experts had a mean of 18.1 ± 10.2 years of experience. The grade distribution (A, B, C) differed significantly ( P  < 0.0001) between the three propagation velocity settings tested; at the lower speed of 1480 m/s, images were most often graded A, while at the conventional speed of 1540 m/s, they were most often graded C. Regardless of the scanning plane, the thicker the fatty layer of the abdominal wall in a given plane, the lower the preferred speed ( P  < 0.0001). Conclusion: The construction of images taking into account ultrasound propagation velocities lower than 1540 m/s can improve significantly the quality of images obtained during mid‐trimester fetal ultrasonography in obese women. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.